Force-tracking control of a novel electric parking brake actuator based on a load-sensing, continuously variable transmission. (September 2016) - Zhang, Lipeng; Yu, Wei; Zhao, Xun; Meng, Aihong; Muhammad, Fahad
For the existing electric parking brake system which is used as a secondary brake system, accurate rear-wheel slip control has not been realized. In addition, the time spent to produce the required braking force after the electric parking brake button is pressed is too long, which reduces the system's response speed. All the above means that the vehicle risks a loss in stability and a braking distance that is too large. To solve these problems, the clamping force should be controlled, and the velocity of the clamping mechanism should be increased in the idle stroke. In this paper, on the assumptions that the motor speed is limited and that the length of the idle stroke is hard to identify because of abrasion of the friction pads, a variable transmission and a novel electric parking brake actuator are designed to reduce the clamping time. In the novel electric parking brake system, the belt reducer of the existing electric parking brake is replaced by a load-sensing, continuously variable transmission, in which the reduction ratio changes with the load torque. Additionally, a reduced-order observer is presented to estimate the motor speed, and a sliding-mode controller is designed to control the clamping force. The controller is robust against uncertainties and disturbance of the parameters. The mathematical model of the system is initially constructed using MATLAB/Simulink to simulate the behaviours of the novel actuator. Then the designed control system for various adhesion coefficient conditions involving an abrupt change in the road friction is investigated. As a result, the effectiveness of the sliding-mode controller is validated by simulations, and the comprehensive performance of the actuator is significantly improved.